The Need for Systems Integration for Youth with a Disability Experiencing Homelessness - Fudge Schormans, Ann (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Youth with a disability are overrepresented among homeless youth and face unique vulnerabilities both in the youth shelter system and when housed. This article shares findings from a study of youth in three sites in southern Ontario, Canada, who identify with a disability and who have experienced homelessness. These findings demonstrate that being housed does not reduce financial vulnerability, social vulnerability, or the vulnerability that comes with negotiating the regulations and rules of landlord/tenant relationships. In order to address the systems disjunctures faced by the youth in our study, we argue for systems integration that focuses beyond homelessness and fairly distributes the burden for integration across a range of services that are currently inaccessible for youth with a disability who are homeless.